THE WAYS TO IMPROVE THE EFFICIENCY OF THE ROLLING STOCK TECHNICAL DIAGNOSTICS - Tetter, V. Yu.; Tetter, A. Yu. (Science and Transport Progress, 2008)
The necessity of use of diagnostic means of the rolling stock is proved. The examples of introduction are presented. The ways for increasing the reliability of diagnostics are offered.